Proposing a new conceptualisation for modern sport based on environmental and regulatory constraints: implications for research, coach education and professional practice. Issue 3 (3rd July 2022) - Collins, Loel; Carson, Howie J.
ABSTRACT: Recent expansion of the sporting domain has meant sports have lacked distinct definitions. These definitions have pertained to specific activities and/or a general perception of an assumed experience, which arguably misunderstands these modern sports. While growth in this domain is encouraging, a clear understanding of modern sports remains a requirement for optimal research, coaching practice and participation. Therefore, we critically consider the difference between these types of sport. In an attempt to address this, the article revisits current definitions of these modern, non-competitive, sports. Specifically, we exemplify issues of conflation within research as justification for our desired clarity. Secondly, we propose a two-dimensional conceptual framework to meaningfully differentiate between these sporting domains and finally, propose several implications for future research, education and applied practice. We hope this article brings clarity within research and the potential positive flow to enhancing education to achieve appropriate outcomes for various participants.